Aktivitas Antioksidan dan Fitokimia dari Ekstrak Etil Asetat Pucuk Idat (Cratoxylum glaucum) - Mahardika, Robby Gus; Roanisca, Occa (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2018)
Neutralizing free radicals can use both synthetic and natural antioxidant compounds. Although synthetic antioxidant compounds are more active, but lately the use of synthetic antioxidants is being reduced because they are reported to have carcinogenic side effects. Natural antioxidant compounds found in plants are phenolic groups such as flavonoids, tannins, xanthones, and anthraquinones. This compound is widely found in the genus Cratoxylum where one of the species is pucuk idat (Cratoxylum glaucum). Pucuk idat are often used by people of Bangka as a flavoring dish and are believed to be traditional medicine to facilitate breastfeeding, tighten skin, treat fever, cough, and diarrhea. The increasing of antioxidants needs and lots efficacy of pucuk idat, hence this study aims to determine the antioxidant activity of ethyl acetate extract Cratoxylum glaucum. The antioxidant test in this study used the DPPH (Diphenylpicrylhydrazyl) method and vitamin C as a positive control. The results of this study indicate that the extract of ethyl acetate Cratoxylum glaucum has strong antioxidant activity with value IC50 32,213 Î¼g / mL. Phytochemical content itself includes hydroquinone phenols (tannins), flavonoids, and steroids. This shows that ethyl acetate extract Cratoxylum glaucum can be used as natural antioxidant.